Development of a Career Enhancement Training is Inherent Part of an Educational Project - Gabdrakhmanova R.G.; Khusainova R.M.; Chirkina S.E.; Asaphova E.V.; Golovanova I.I.; Telegina N.V. (Psihologiceskaâ nauka i obrazovanie (2007), 2015)
Career enhancement training is common for teachers, yet participating in the project requires special training. Project training courses expose project objectives and allow getting necessary skills, materials and tools to determine the results. Training course have to include a content for which teachers will need to make a report. R. A. Valeeva, Ph.D., Professor, was the manager of a project “Development and testing of new modules and rules for the implementing of the basic bachelor educational program in an "Education and Pedagogy" aggregated group (psycho-pedagogical training direction), which implies academic mobility of students studying education science (non-educational training directions) in the context of networking”. To implement the project, it was decided to establish close partnerships with five higher educational institutions in the country. We have developed training courses to prepare teaching and resource staff of our university, as well as our partners to strong partnership in the project execution.